PENERAPAN POLA HIDUP BERSIH DAN SEHAT UNTUK MENINGKATKAN IMUNITAS TUBUH DI DESA KALIRANCANG, ALIAN, KEBUMEN - Yuni Kartika; Farida Pramestian; Nahdiah Masayu; Fathurrohmah Hasanah; Febri Fera; Ridwan Arifin (Universitas Negeri Surabaya, 2021)
A clean and healthy lifestyle (PHBS) is a set of behaviors that are practiced on the basis of awareness as a result of learning that makes a person, family, group or community able to help themselves (independently) in the health sector and play a role in realizing public health. The student group KKN BMC UNNES 2020 has a mission to make the people of Kalirancang Village, Alian District, Kebumen Regency, Central Java aware of implementing a clean and healthy lifestyle (PHBS) in their daily life, especially during the Covid-19 pandemic. The method of implementing KKN includes socialization and counseling on the application of a clean and healthy lifestyle (PHBS) directly to the people of Kalirancang Village, Alian District, which is the object. Several activities are carried out, such as weighing the baby every month, using clean water, washing hand use soap, healthy eating patterns, and doing bodily activities. The results achieved through these activities are being able to make people aware of the importance of implementing a clean and healthy lifestyle (PHBS) and can provide knowledge to the community regarding how to properly implement a clean and healthy lifestyle so that people can implement PHBS regularly in their daily life.